The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.4038/agrieast.v11i1.33
|View full text |Cite
|
Sign up to set email alerts
|

Plant defense-related enzymes against pathogens: a review

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
54
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 57 publications
4
54
0
2
Order By: Relevance
“…This result suggests that the Agave enzymes are involved in defense mechanisms. The inhibition observed was lower than that reported for other plant chitinases [3,54]; however, it is known that plants overexpress a pull of chitinases, glucanases, and others PR proteins that act synergistically to fight pathogen infections [65]. These inhibitory concentration values are similar to those reported for barley class I chitinase of 80 and 200 lg [66].…”
Section: Discussionsupporting
confidence: 64%
“…This result suggests that the Agave enzymes are involved in defense mechanisms. The inhibition observed was lower than that reported for other plant chitinases [3,54]; however, it is known that plants overexpress a pull of chitinases, glucanases, and others PR proteins that act synergistically to fight pathogen infections [65]. These inhibitory concentration values are similar to those reported for barley class I chitinase of 80 and 200 lg [66].…”
Section: Discussionsupporting
confidence: 64%
“…The activity of defense-related enzymes, peroxidase, and polyphenoloxidase is known to be induced via systemic resistance of many infected plants with fungal pathogens (Prasannath, 2017). These enzymes act as elicitors of the phenylpropanoid pathway, resulting in the biosynthesis of a diverse array of plant metabolites such as phenolic compounds, flavonoids, tannins, and lignin.…”
Section: Discussionmentioning
confidence: 99%
“…These products can provide defense in plants against pathogenic attack (Walters et al, 2013 andMayer, 2006). Many studies indicated a greater accumulation of phenolics as a result of increasing the activities of these oxidative enzymes which could offer protection against plant diseases (Reddy et al, 2014 andPrasannath, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reinforcing the cell wall to prevent further pathogen ingress is the most common response of the infected host plant. Cell wall enhancement is always achieved by cellulose synthesis, lignification, and callose deposition [45]. Histochemical staining showed that there were no significant changes in the cell morphology of ZQK9 after P. capsici infection, while the epidermal cells of E31 were disintegrated (Fig 2).…”
Section: Cell Wall Modificationmentioning
confidence: 97%